Conflict or coexistence? Synergies between nature conservation and traditional tea industry development in Wuyishan National Park, China - Wang, Bojie; He, Siyuan; Min, Qingwen; Yang, Xiao (Frontiers in Sustainable Food Systems, 2023)
Traditional agricultural industries in protected areas (PAs) provide opportunities for both nature conservation and the wellbeing of local residents. However, knowledge about the synergies between nature conservation and traditional agricultural industries is still limited. This research takes the traditional tea industry in Wuyishan National Park as a case to identify and examine the synergistic mechanism between forest conservation and industrial development, why traditional agricultural industries are necessary to the regional economy, and how they secure local livelihoods as well as achieve conservation goals. We conducted literature research and semi-structured interviews with Wuyishan National Park Authority, local government administrations, enterprises and small-scale farmers. The results were obtained through a two-stage mixed method of grounded theory and system dynamics. The findings revealed that: (1) Traditional agricultural industries in PAs were resilient and adaptable in the face of external changes, in which traditional culture and ecological awareness played an important role. (2) Small-scale agri-industries were vulnerable to external shocks, but they also have advantages in terms of moderate agglomeration and standardization, risk perception and response, and market-based diversification of production. (3) The synergetic process of traditional agricultural industries and conservation is mainstreaming biodiversity by cooperation among the government, the park agency, and local people. Thus, we suggested that the local government should work together with the PA management agencies to re-evaluate the existence of traditional agricultural industries for their necessity in the regional economy and the feasibility of improving local livelihoods.